The Effects of Sungkai Leaf and Cinnamon Bark Extracts on MDA and IL-10 in MSG Induced Chronic Kidney Disease in Wistar Rats - Afrianti, Dina; Maulana, Mochamad Rizal; Sakdiah, Siti; Febriyani, Erisa; Wahyudi, Wahyudi; Ali, Irwan (Medical Laboratory Technology Journal, 2025)
Monosodium glutamate (MSG) is known to trigger oxidative stress and inflammation, contributing to kidney tissue damage. This study aimed to evaluate the protective effects of sungkai leaf extract (Peronema canescens Jack) and cinnamon bark extract (Cinnamomum burmannii) on kidney histology, as well as malondialdehyde (MDA) and interleukin-10 (IL-10) levels in male Wistar rats induced with excessive MSG. A total of 30 rats were divided into six groups: normal control, positive control (MSG only), and four treatment groups receiving MSG alongside sungkai leaf extract (28 mg or 56 mg) or cinnamon bark extract (4% or 8%) for 10 days. MDA and IL-10 levels were measured using ELISA, and kidney tissue was examined histologically. The results showed that both extracts significantly reduced MDA (P= 0,000)  levels and increased IL-10 (P= 0,000)   levels compared to the positive control. The most prominent protective effect was observed in the group treated with 56 mg of sungkai leaf extract, followed by the 8% cinnamon bark group. Histopathological analysis revealed notable improvements in kidney structure, approaching normal conditions in treated groups. These findings suggest that sungkai leaf and cinnamon bark extracts, particularly at higher doses, offer protective benefits against MSG-induced kidney damage through antioxidant and anti-inflammatory mechanisms.